The methodological debate on the interartistic study of painting-literature: Francisco Bores (1898-1972) and his avant-garde artistic circle - Faura González, Judit (Eikón / Imago, 2024)
This article aims to examine how the methodological debate related to the study of the interaction between painting and literature during the early avant-garde has developed, using the case of Francisco Bores, a painter associated with the School of Paris, and his close artistic circle as a paradigmatic example. From the perspective of Comparative Literature, Visual Studies and Semiotics, scholars have sought to examine both similarities and divergences between the two manifestations. Through this interdisciplinary perspective, the aim is to explore this period using the works of these artists as a starting point to incorporate various theoretical contributions present in contemporary historiography, which have focused on the relationship between art and literature.